Preparation method of nickel-based gel-carbon nitride composite photocatalyst and application of nickel-based gel-carbon nitride composite photocatalyst in CO2 reduction
The photocatalyst is prepared by composited with nickel-based gel and graphite phase carbon nitride, which solves the problem of insufficient photocatalytic activity of pure g-C3N4, significantly improves CO2 reduction performance and catalytic efficiency, and achieves efficient photocatalytic CO2 reduction.
Patent Information
- Application Number
- CN202411419974.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
As a photocatalyst, pure graphite phase carbon nitride (g-C3N4) has disadvantages such as small specific surface area, high photogenerated carrier recombination rate, and easy photogenerated electron hole recombination, which limits its photocatalytic activity and requires modification to improve adsorption performance. and photocatalytic reduction properties.
The photocatalyst is prepared by combining nickel-based gel and g-C3N4. The nickel-based gel and g-C3N4 are uniformly dispersed by ultrasonic treatment to improve the separation and transfer of photogenerated carriers and improve the photocatalytic activity.
It significantly improves the CO2 reduction performance of g-C3N4, with a catalytic efficiency of about 4 times that of pure g-C3N4, has strong stability, environmentally friendly, and has high electron-hole separation efficiency, and is suitable for gas-solid phase CO2 reduction.
Smart Images

Figure CN119303634A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photocatalytic material preparation, and specifically relates to a method for preparing a nickel-based gel-carbon nitride composite photocatalyst and application thereof in CO2 reduction. Background Art
[0002] In order to reduce the greenhouse effect and global warming caused by CO2 emissions, using solar photocatalysis to reduce CO2 to high-value-added chemical raw materials is one of the effective ways to alleviate the greenhouse effect and energy shortage. Among them, designing and developing photocatalysts with excellent performance is a key way to improve catalytic activity.
[0003] As a new type of inorganic non-metallic photocatalyst, graphite carbon nitride (g-C3N4) has attracted much attention due to its good optical and physicochemical properties. g-C3N4 has the advantages of adjustable band structure, high physicochemical stability and visible light response. The band gap of g-C3N4 is about 2.7eV, which enables g-C3N4 to absorb visible light and has a high solar energy utilization efficiency. In addition, its surface contains rich amino groups, which is conducive to CO2 adsorption. However, pure g-C3N4 has the disadvantages of small specific surface area, high recombination rate of photogenerated carriers, and easy recombination of photogenerated electrons and holes, which greatly limit its photocatalytic activity.
[0004] Therefore, how to improve the photocatalytic activity of g-C3N4 has become an urgent problem to be solved. The commonly used method requires modification of g-C3N4 to improve the adsorption performance and photocatalytic reduction performance of g-C3N4 and shorten the photocatalytic reaction time. Common modification methods mainly include morphology control, element doping, co-catalyst modification, heterogeneous structure construction, etc.
[0005] The present invention is a preparation method of a novel photocatalyst by compositely preparing an environmentally friendly nickel-based gel and g-C3N4, which can effectively promote the separation and transfer of photogenerated carriers and is beneficial to the transfer of photogenerated carriers at the interface, thereby obtaining better photocatalytic activity. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a nickel-based gel-carbon nitride composite photocatalyst. The composite catalyst prepared by the method effectively improves the CO2 reduction performance of carbon nitride and is more environmentally friendly than other types of catalysts.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a nickel-based gel-carbon nitride composite photocatalyst, the method for preparing the catalyst comprising the following steps:
[0009] (1) Weigh a certain weight of urea and place it in a crucible, place it in a muffle furnace with a cover for primary calcination, cool it to room temperature, wash it with ethanol and deionized water, and then dry it. The dried block g-C3N4 is placed in the crucible again, and calcined twice in a muffle furnace without a cover. After cooling, it is ground to obtain ultrathin g-C3N4;
[0010] (2) Boc-glutamic acid and octadecylamine are mixed in dichloromethane, and then 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1-hydroxybenzotriazole are added to the mixture, and stirred at room temperature for 72 hours. After stirring, the mixture is filtered to separate a white solid, and the white solid is washed with dichloromethane, and then dissolved in tetrahydrofuran. The solution is precipitated by adding water, filtered and vacuum dried at 60° C., and then ground to obtain a white powder N,N'-bis(octadecyl)-L-boc-glutamic acid diamine;
[0011] (3) dispersing the white powder N,N'-bis(octadecyl)-L-boc-glutamic acid diamine obtained in step (2) into dichloromethane and adding trifluoroacetic acid, stirring at room temperature for 3 hours, then removing the solvent using a rotary evaporator, dissolving the residual white solid in tetrahydrofuran, and then pouring the dissolved solution into a saturated sodium bicarbonate aqueous solution to obtain a milky white suspension, filtering the suspension and washing it with deionized water, vacuum drying it at 60°C and grinding it to obtain a white powder N,N'-bis(octadecyl)-L-glutamic acid diamine;
[0012] (4) dispersing the white powder N,N'-bis(octadecyl)-L-glutamic acid diamine obtained in step (3) in dichloromethane and stirring for 30 minutes to obtain a solution, then adding nicotinic acid to the solution, stirring at 0°C for 30 minutes, then adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1-hydroxybenzotriazole to the mixed solution, stirring the mixed solution at room temperature for 72 hours, and after the stirring is completed, removing the solvent by rotary evaporation, dissolving the residual white solid in tetrahydrofuran, pouring the solution into a saturated sodium bicarbonate aqueous solution to obtain a milky white suspension, filtering the suspension and washing with deionized water, vacuum drying at 60°C, and grinding to obtain L-glutamate;
[0013] (5) The L-glutamate obtained in step (4), the g-C3N4 in step (1), nickel chloride hexahydrate and ethanol are mixed and ultrasonically treated in a centrifuge tube until they are uniformly dispersed. After standing for 6 hours, the solid is separated by multiple centrifugation and washed with ethanol. After washing, the solid is vacuum dried and ground to obtain a nickel-based gel-carbon nitride composite photocatalyst.
[0014] Preferably, the temperature raising program of the muffle furnace in the first calcination in step (1) is to heat to 550° C. at 2° C. / min and calcine for 4 hours.
[0015] Preferably, the temperature raising program of the muffle furnace in the secondary calcination in step (1) is to heat to 500° C. at 5° C. / min and calcine for 2 h.
[0016] Preferably, in step (2), Boc-glutamic acid is 2.47 g, octadecylamine is 5.39 g, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 4.02 g, and 1-hydroxybenzotriazole is 2.97 g. The amount of dichloromethane used is 200 mL, and the amount of tetrahydrofuran used is 20 mL.
[0017] Preferably, the stirring speed in step (2) is 500 r / min, the stirring speed in step (3) is 500 r / min, and the stirring speed in step (4) is 500 r / min.
[0018] Preferably, in step (3), the amount of white powder N,N'-bis(octadecyl)-L-boc-glutamic acid diamine is 3.575 g, the amount of dichloromethane is 50 mL, the amount of trifluoroacetic acid is 8 mL, the amount of tetrahydrofuran is 20 mL, and the amount of saturated sodium bicarbonate aqueous solution is 300 mL.
[0019] Preferably, in step (4), the white powder N,N'-bis(octadecyl)-L-glutamic acid diamine is 0.65 g, nicotinic acid is 0.66 g, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 0.23 g, 1-hydroxybenzotriazole is 0.16 g, the amount of dichloromethane is 60 mL, the amount of tetrahydrofuran is 20 mL, and the amount of saturated sodium bicarbonate aqueous solution is 300 mL.
[0020] Preferably, in step (5), the mass ratio of gel L-glutamate to g-C3N4 is 1:3-7;
[0021] Preferably, in step (5), the gel L-glutamate is 20 mg, the g-C3N4 is 100 mg, the nickel chloride hexahydrate is 35 mg, the ethanol is 3 ml, the ultrasonic time is 30 min, the temperature is room temperature 25°C, and the centrifugal speed is 10000 r / min.
[0022] The application of the composite photocatalyst prepared by the preparation method of the nickel-based gel-carbon nitride composite photocatalyst in reducing CO2.
[0023] The beneficial effects of the present invention are:
[0024] 1. The carbon nitride and gel selected by the present invention are environmentally friendly, and the gel can be recycled by ethanol. Its main component is L-glutamate, which is harmless to the human body and the environment. Carbon nitride belongs to inorganic non-metallic materials and is also non-toxic to the environment. The precursor material of carbon nitride is urea, which has low cost, stable properties, and simple and easy-to-obtain raw materials.
[0025] 2. The nickel-based gel-carbon nitride composite photocatalyst of the present invention has the advantages of strong stability, strong light capture ability, high electron-hole pair separation efficiency, excellent photocatalytic performance, etc. It can separate photogenerated carriers more effectively, especially when applied to gas-solid phase CO2 reduction, it has strong photocatalytic activity, which is about 4 times the catalytic performance of pure carbon nitride, greatly improving the catalytic efficiency, and has good application prospects in photocatalytic CO2 reduction to usable fuel.
[0026] 3. The addition of nickel-based gel in the present invention improves the reduction performance of carbon nitride, reduces the charge transfer resistance of the combined material nickel-based gel-carbon nitride composite photocatalyst, increases the interface charge transfer rate, and improves the electron-hole separation efficiency. Compared with carbon nitride, the nickel-based gel-carbon nitride composite photocatalyst in the present invention has a higher photocurrent, a better separation effect of photogenerated electrons and holes, a stronger photocatalytic ability of the catalyst, and its recombination of photogenerated electrons and holes is suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart of a method for preparing a nickel-based gel-carbon nitride composite catalyst;
[0028] Figure 2 Transmission electron microscope image and scanning electron microscope image of the nickel-based gel-carbon nitride composite catalyst obtained when the mass ratio of L-glutamate to carbon nitride is 1:5;
[0029] Figure 3 This is a comparison chart of the photocatalytic CO2 effects of carbon nitride and nickel-based gel composites with different proportions.
[0030] Figure 4 The UV diffuse reflection diagrams of Example 1 and Comparative Examples 1 and 2 are shown.
[0031] Figure 5 The electrochemical impedance spectra of Example 1 and Comparative Examples 1 and 2 are shown.
[0032] Figure 6 The transient photocurrent spectra of Example 1 and Comparative Examples 1 and 2 are shown. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0034] Example 1: L-glutamate and carbon nitride mass ratio 1:5
[0035] (1) Weigh 10g of urea with a precision electronic balance and place it in a 50mL covered crucible. Then transfer the covered crucible to a muffle furnace, set the heating rate to 2℃ / min, heat to 550℃, and maintain the temperature for 4h. Then cool naturally to room temperature, grind the resulting product into powder, wash it twice with ethanol and deionized water respectively, place it in a vacuum drying oven with a drying temperature of 60℃, and dry it until it is completely free of moisture. Transfer the dried block g-C3N4 to an uncovered crucible again, and transfer it to a muffle furnace, set the heating rate to 5℃ / min, heat to 500℃, maintain the temperature for 2h, cool to room temperature, and grind it into powder to obtain ultrathin g-C3N4.
[0036] (2) 2.47 g of Boc-glutamic acid and 5.39 g of octadecylamine were mixed in 200 mL of dichloromethane, and then 4.02 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 2.97 g of 1-hydroxybenzotriazole were added to the mixture. The mixture was poured into a 250 mL flask and stirred at room temperature at a speed of 500 r / min for 72 h. After stirring, the mixture was separated by suction filtration to obtain a white solid, which was washed three times with dichloromethane and then dissolved in 20 mL of tetrahydrofuran. The solution was precipitated by adding 300 mL of water, filtered and vacuum dried at 60° C. After drying, the white powder N,N'-bis(octadecyl)-L-boc-glutamic acid diamine was obtained by grinding.
[0037] (3) Take a 100 mL flask, add 3.575 g of the white powder N, N'-bis (octadecyl) -L-boc- glutamic acid diamine prepared in step (2), 50 mL of dichloromethane and 8 mL of trifluoroacetic acid, stir at room temperature at a speed of 500 r / min for 3 h, then use a rotary evaporator to remove the solvent, dissolve the residual white solid in 20 mL of tetrahydrofuran, and then pour the dissolved solution into 300 mL of saturated sodium bicarbonate aqueous solution to obtain a milky white suspension, filter the suspension and wash with deionized water, vacuum dry at 60 ° C and grind to obtain a white powder N, N'-bis (octadecyl) -L- glutamic acid diamine.
[0038] (4) Take a 100 mL flask, add 0.65 g of the white powder N, N'-bis (octadecyl) -L-glutamic acid diamine prepared in step (3), 60 mL of dichloromethane, stir at a speed of 500 r / min for 30 min, then add 0.66 g of nicotinic acid to the above solution, stir at a speed of 500 r / min for 30 min at 0 ° C, then add 0.23 g of 1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride and 0.16 g of 1-hydroxybenzotriazole to the solution, and stir the solution at room temperature at 500 r / min for 72 h. After stirring, the solvent is removed by rotary evaporation, the residual white solid is dissolved in 20 mL of tetrahydrofuran, and the solution is poured into 300 mL of saturated sodium bicarbonate aqueous solution to obtain a milky white suspension, the suspension is filtered and washed with deionized water, and vacuum dried at 60 ° C and ground to obtain L-glutamate.
[0039] (5) In a 10 mL centrifuge tube, 20 mg of L-glutamate prepared in step (4), 100 mg of ultrathin g-C3N4 prepared in step (1), 35 mg of nickel chloride hexahydrate and 3 mL of ethanol were mixed, and the mixture was ultrasonically treated for 30 min until it was evenly dispersed. After standing for 6 h, the solid was centrifuged several times and washed with ethanol. After washing, the solid was dried in a vacuum drying oven at 60° C. to obtain a nickel-based gel-carbon nitride composite photocatalyst (labeled as Ni-gel / CNNS-5).
[0040] The composite catalyst was tested by transmission electron microscopy and scanning electron microscopy, and the sample morphology was as follows: Figure 2 shown.
[0041] Example 2: L-glutamate and carbon nitride mass ratio 1:3
[0042] The preparation method is basically the same as that in Example 1, except that: in step (5), 20 mg of L-glutamate prepared in step (4), 60 mg of ultrathin g-C3N4 prepared in step (1), 35 mg of nickel chloride hexahydrate and 3 mL of ethanol are mixed in a 10 mL centrifuge tube, and the mixture is ultrasonically treated for 30 min until it is evenly dispersed. After standing for 6 h, the solid is centrifuged several times and washed with ethanol. After washing, the solid is dried in a vacuum drying oven at 60°C to obtain a nickel-based gel-carbon nitride composite photocatalyst (labeled as Ni-gel / CNNS-3).
[0043] Example 3: L-glutamate and carbon nitride mass ratio 1:7
[0044] The preparation method is basically the same as that in Example 1, except that: in step (5), 20 mg of L-glutamate prepared in step (4), 140 mg of ultrathin g-C3N4 prepared in step (1), 35 mg of nickel chloride hexahydrate and 3 mL of ethanol are mixed in a 10 mL centrifuge tube, and the mixture is ultrasonically treated for 30 min until it is evenly dispersed. After standing for 6 h, the solid is centrifuged several times and washed with ethanol. After washing, the solid is dried in a vacuum drying oven at 60°C to obtain a nickel-based gel-carbon nitride composite photocatalyst (labeled as Ni-gel / CNNS-7).
[0045] Comparative Example 1: Pure Carbon Nitride
[0046] Carbon nitride was prepared using only the preparation method of step (1) in Example 1. 10 g of urea was weighed with a precision electronic balance and placed in a 50 mL covered crucible. The covered crucible was then transferred to a muffle furnace, the heating rate was set to 2 ° C / min, heated to 550 ° C, and maintained at the temperature for 4 hours. Then it was naturally cooled to room temperature, the resulting product was ground into powder, washed twice with ethanol and deionized water, respectively, and placed in a vacuum drying oven with a drying temperature of 60 ° C, and dried until completely free of moisture. The dried block g-C3N4 was transferred again to an uncovered crucible and transferred to a muffle furnace. The heating rate was set to 5 ° C / min, heated to 500 ° C, maintained at the temperature for 2 hours, and ground into powder after cooling to room temperature to obtain ultrathin g-C3N4 (labeled as CNNS).
[0047] Comparative Example 2: Nickel-based gel
[0048] The preparation method is basically the same as that in Example 1, except that in step (5), a 10 mL centrifuge tube is taken, 20 mg of L-glutamate prepared in step (4), 35 mg of nickel chloride hexahydrate and 2 mL of ethanol are added to obtain a nickel-based gel (labeled as Ni-gel).
[0049] The CO2 reduction products of the composite catalyst, gel and ultrathin g-C3N4 were detected using the Labsolar-6A all-glass automatic online trace gas analysis system of Beijing Perfect Light Technology Co., Ltd. The light source used was a xenon lamp of Beijing Perfect Light Technology Co., Ltd., model PLS-SXE300D, and the reduction products were detected using a Zhejiang Fuli GC 9790Ⅱ gas chromatograph. The test results are shown in the figure. Figure 3 shown.
[0050] Figure 3 The photocatalytic CO2 effect comparison of g-C3N4 and nickel-based gel composites with different proportions is shown in the attached figure. Figure 3It can be seen that the CO2 reduction efficiency of the nickel-based gel-carbon nitride composite photocatalyst prepared in Examples 1-3 is improved compared with carbon nitride (CNNS) and nickel-based gel (Ni-gel). When the mass ratio of L-glutamate to carbon nitride is 1:5, the catalytic efficiency of the prepared nickel-based gel-carbon nitride composite photocatalyst (Ni-gel / CNNS-5) is the highest, which is 7.7062 μmol·g -1 ·h -1 , about the original carbon nitride (2.0397 μmol·g -1 ·h -1 ) and about 4 times that of pure gel (1.9945 μmol·g -1 ·h -1 ) by 4 times, and the catalytic efficiency is greatly improved. In the nickel-based gel-carbon nitride composite photocatalyst prepared by the present invention, the nickel-based gel and carbon nitride play a synergistic role in the catalytic process, which can greatly improve the catalytic performance.
[0051] Figure 4 The ultraviolet diffuse reflection diagrams of Example 1 and Comparative Examples 1 and 2 are shown in the attached Figure 4 It can be seen from the results of the ultraviolet diffuse reflection test that the light absorption band edge of the carbon nitride (CNNS) prepared in Comparative Example 1 is about 404nm, the light absorption band edge of the nickel-based gel (Ni-gel) in Comparative Example 2 is about 350nm, and the absorption edge of the nickel-based gel-carbon nitride composite photocatalyst (Ni-gel / CNNS-5) prepared in Example 1 is red-shifted to about 408nm. The light absorption range of the composite catalyst prepared by combining the nickel-based gel and carbon nitride materials is improved.
[0052] Figure 5 The electrochemical impedance spectra of Example 1 and Comparative Examples 1 and 2 are shown in the attached Figure 5 It can be seen that the fitting radius of the nickel-based gel-carbon nitride composite photocatalyst (Ni-gel / CNNS-5) prepared in Example 1 is smaller than that of the carbon nitride (CNNS) prepared in Comparative Example 1, indicating that the addition of nickel-based gel improves the reduction performance of carbon nitride, reduces the charge transfer resistance of the combined material nickel-based gel-carbon nitride composite photocatalyst (Ni-gel / CNNS-5), increases the interface charge transfer rate, and improves the electron-hole separation efficiency.
[0053] Figure 6 The transient photocurrent spectra of Example 1 and Comparative Examples 1 and 2 are shown in FIG. Figure 6 It can be seen that the photocurrent intensity of the nickel-based gel-carbon nitride composite photocatalyst (Ni-gel / CNNS-5) is greater than that of the nickel-based gel (Ni-gel), indicating that the combination with carbon nitride makes the separation of photogenerated electrons and holes in the nickel-based gel better, and the recombination of photogenerated electrons and holes is inhibited.
[0054] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a nickel-based gel-carbon nitride composite photocatalyst, characterized in that: The method for preparing the catalyst comprises the following steps: (1) Weigh a certain weight of urea and place it in a crucible, place it in a muffle furnace with a cover for primary calcination, cool it to room temperature, wash it with ethanol and deionized water, and then dry it. The dried block g-C3N4 is placed in the crucible again, and calcined twice in a muffle furnace without a cover. After cooling, it is ground to obtain ultrathin g-C3N4; (2) Boc-glutamic acid and octadecylamine are mixed in dichloromethane, and then 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1-hydroxybenzotriazole are added to the mixture, and stirred at room temperature for 72 hours. After stirring, the mixture is filtered to separate a white solid, and the white solid is washed with dichloromethane, and then dissolved in tetrahydrofuran. The solution is precipitated by adding water, filtered and vacuum dried at 60° C., and then ground to obtain a white powder N,N'-bis(octadecyl)-L-boc-glutamic acid diamine; (3) dispersing the white powder N,N'-bis(octadecyl)-L-boc-glutamic acid diamine obtained in step (2) into dichloromethane and adding trifluoroacetic acid, stirring at room temperature for 3 hours, then removing the solvent using a rotary evaporator, dissolving the residual white solid in tetrahydrofuran, and then pouring the dissolved solution into a saturated sodium bicarbonate aqueous solution to obtain a milky white suspension, filtering the suspension and washing it with deionized water, vacuum drying it at 60°C and grinding it to obtain a white powder N,N'-bis(octadecyl)-L-glutamic acid diamine; (4) dispersing the white powder N,N'-bis(octadecyl)-L-glutamic acid diamine obtained in step (3) in dichloromethane and stirring for 30 minutes to obtain a solution, then adding nicotinic acid to the solution, stirring at 0°C for 30 minutes, then adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 1-hydroxybenzotriazole to the solution, stirring the solution at room temperature for 72 hours, and after stirring, removing the solvent by rotary evaporation, dissolving the residual white solid in tetrahydrofuran, and pouring the solution into a saturated sodium bicarbonate aqueous solution to obtain a milky white suspension, filtering the suspension and washing with deionized water, drying in vacuo at 60°C, and grinding to obtain L-glutamate; (5) The L-glutamate obtained in step (4), the g-C3N4 in step (1), nickel chloride hexahydrate and ethanol are mixed and ultrasonically treated in a centrifuge tube until they are uniformly dispersed. After standing for 6 hours, the solid is separated by multiple centrifugation and washed with ethanol. After washing, the solid is vacuum dried and ground to obtain a nickel-based gel-carbon nitride composite photocatalyst.
2. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: The temperature raising program of the muffle furnace in the first calcination in the step (1) is to heat to 550° C. at 2° C. / min and calcine for 4 hours.
3. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: The temperature raising program of the muffle furnace in the secondary calcination in step (1) is to heat to 500° C. at 5° C. / min and calcine for 2 h.
4. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: In the step (2), the amount of Boc-glutamic acid is 2.47 g, the amount of octadecylamine is 5.39 g, the amount of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 4.02 g and the amount of 1-hydroxybenzotriazole is 2.97 g, the amount of dichloromethane used is 200 mL, and the amount of tetrahydrofuran used is 20 mL.
5. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: The stirring speed in step (2) is 500 r / min, the stirring speed in step (3) is 500 r / min, and the stirring speed in step (4) is 500 r / min.
6. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: In the step (3), the white powder N,N'-bis(octadecyl)-L-boc-glutamic acid diamine is 3.575 g, the amount of dichloromethane is 50 mL, the amount of trifluoroacetic acid is 8 mL, the amount of tetrahydrofuran is 20 mL, and the amount of saturated sodium bicarbonate aqueous solution is 300 mL.
7. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: In the step (4), the white powder N,N'-bis(octadecyl)-L-glutamic acid diamine is 0.65 g, nicotinic acid is 0.66 g, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride is 0.23 g, 1-hydroxybenzotriazole is 0.16 g, the amount of dichloromethane is 60 mL, the amount of tetrahydrofuran is 20 mL, and the amount of saturated sodium bicarbonate aqueous solution is 300 mL.
8. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: In the step (5), the mass ratio of L-glutamate to g-C3N4 is 1:3-7.
9. The method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to claim 1, characterized in that: In the step (5), the amount of L-glutamate is 20 mg, the amount of g-C3N4 is 100 mg, the amount of nickel chloride hexahydrate is 35 mg, the amount of ethanol is 3 ml, the ultrasonic time is 30 min, the temperature is room temperature 25° C., and the centrifugal speed is 10000 r / min.
10. Use of the composite photocatalyst prepared by the method for preparing the nickel-based gel-carbon nitride composite photocatalyst according to any one of claims 1 to 9 in reducing CO2.